Multivariate searches for single top quark production with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2007)
We present a search for electroweak production of single top quarks in the s-channel (pp̄→tb̄+X) and t-channel (pp̄→tqb̄+X) modes. We have analyzed 230pb-1 of data collected with the D0 detector at the Fermilab Tevatron Collider at a center-of-mass energy of s=1.96TeV. No evidence for a single top quark signal is found. We set 95% confidence level upper limits on the production cross sections, based on binned likelihoods formed from a neural network output. The observed (expected) limits are 6.4 pb (4.5 pb) in the s-channel and 5.0 pb (5.8 pb) in the t-channel. © 2007 The American Physical Society.